22 Surgical aortic valve replacement (SAVR) upon right ventricular function: a cardiac mri study. (26th April 2015) - Musa, TA; Uddin, A; Fairbairn, TA; Dobson, LE; Steadman, C; Kidambi, A; Motwani, M; Ripley, DP; McDiarmid, AK; Swoboda, P; Erhayiem, B; Garg, P; et al.
Abstract : Background: Right ventricular function is of prognostic importance in a variety of clinical settings but its complex anatomic geometry can pose a challenge to 2-dimensional imaging modalities. Right ventricular dysfunction is thought to occur following cardiac surgery and independently predicts adverse outcomes. However a clear mechanism for this dysfunction remains undefined. Aim: To accurately assess the effect of SAVR upon right ventricular function in patients treated for severe symptomatic aortic stenosis. Methods: All patients underwent an identical 1.5T CMR protocol before and 6 months after surgery (Intera, Phillips Healthcare, Best, The Netherlands or Avanto, Siemens Medical Systems, Erlangen, Germany). Results: 53 SAVR patients (age 72.7 ± 7.4 years, 72% male, mean EuroSCORE II 1.52 ± 0.95%) were studied. Six received a metallic prosthesis and the remaining 47 (89%) a tissue bioprosthesis. Fourteen (26%) received concomitant coronary bypass grafting, of which 6 involved use of the left internal mammary artery. For the group as a whole, the average bypass time was 105 ± 48 min and average cross clamp time 77 ± 41 min. The average length of stay in intensive care was 3.4 ± 2.4 days. SAVR was associated with a significant decrease in RV ejection fraction and concomitant increase in indexed RVESV at 6 months, with no change in RV mass (Table 1). However, in subgroup analysis of patients without LGE of the left ventricle at baseline, no significant change in RV function was seen following SAVR (p = 0.06). Conclusions: SAVR is associated with a significant reduction in right ventricular ejection fraction at 6 months mediated through an increase in end systolic volume. The presence of LGE may have the potential to identify patients at risk of post-operative RV dysfunction.